Un Triángulo vital para la República: Gran Bretaña, Francia y la Unión Soviética ante la Guerra Civil española - Enrique Moradiellos (Amnis)
This article analyses the impact of the Spanish Civil War upon the unstable European context of the late 1930s and, particularly, upon the reactions towards the conflict of the Democratic Powers, Great Britain and France, on the one hand, and the Soviet Union, on the other. Its fundamental conclusion is that the prickly « Spanish problem » revealed throughout the profound cleavage between the « policy of collective security » as it was understood by the USSR and the « policy of appeasement » as it was practised by the French and British governments. Indeed, the prolonged war in Spain seemed to be a crucial factor in the failure to create a broad diplomatic and military front in Europe against the expansionism of the Axis Powers.